2007
DOI: 10.1093/bioinformatics/btm195
|View full text |Cite
|
Sign up to set email alerts
|

Information theory applied to the sparse gene ontology annotation network to predict novel gene function

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
138
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(141 citation statements)
references
References 55 publications
0
138
0
3
Order By: Relevance
“…The predicted gene/protein function in the NCBI database was searched against InterPro using the available online bioinformatics tool (http://www. uniprot.org) and determined according to Tao et al (2007) and Chitale et al (2009).…”
Section: Data Mining and Annotation Of Putative Tdfsmentioning
confidence: 99%
“…The predicted gene/protein function in the NCBI database was searched against InterPro using the available online bioinformatics tool (http://www. uniprot.org) and determined according to Tao et al (2007) and Chitale et al (2009).…”
Section: Data Mining and Annotation Of Putative Tdfsmentioning
confidence: 99%
“…Guo et al compared a number of network-based and information content-based semantic similarity methods in distinguishing true and false human PPIs, and concluded that the average (AVG) method by Resnik performed best in AUROC analysis [55][56][57][58]. Xu et al compared the AVG and maximum (MAX) methods by Resnik to a number of semantic similarity methods specifically developed for GO, and concluded that the MAX method by Resnik outperforms others when considering the three ontologies of GO either individually or together [55,[59][60][61][62]. More recently, our group developed the Topological Clustering Semantic Similarity (TCSS) method, which uses a novel normalization technique before computing similarity [63].…”
Section: Cellular Location Biological Process Molecular Functionmentioning
confidence: 99%
“…Finally, we evaluate the prediction accuracy using two types of background knowledge -domain and raw knowledge, as opposed to only domain knowledge in their case. Additional related work includes [15], where the authors use a threshold of lowest semantic similarity value to find best-matching term pairs with the goal of predicting molecular functions of genes in Gene Ontology (GO) [16] annotations. Similar to our work, the authors tailor the semantic similarity measures according to fit the structure of GO and their application requirements.…”
Section: Related Workmentioning
confidence: 99%